2011
DOI: 10.1016/j.jbiomech.2010.09.033
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound echo is related to stress and strain in tendon

Abstract: The mechanical behavior of tendons has been well studied in vitro. A noninvasive method to acquire mechanical data would be highly beneficial. Elastography has been a promising method of gathering in vivo tissue mechanical behavior, but it has inherent limitations. This study presents acoustoelasticity as an alternative ultrasound-based method of measuring tendon stress and strain by reporting a relationship between ultrasonic echo intensity (B mode ultrasound image brightness) and mechanical behavior of tendo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
49
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(56 citation statements)
references
References 31 publications
7
49
0
Order By: Relevance
“…As anticipated, ultrasound echo intensity measurements likewise demonstrated volume-dependent changes. Volume-dependent echo intensity changes that are related to pressure changes in inflating lung tissue are analogous to strain-dependent echo intensity changes that are related to stress changes in the stretching tendon [7], and the stiffness-related changes in echo intensity first seen in tendon [9] are here confirmed as compliance-related changes in lung echo intensity.…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…As anticipated, ultrasound echo intensity measurements likewise demonstrated volume-dependent changes. Volume-dependent echo intensity changes that are related to pressure changes in inflating lung tissue are analogous to strain-dependent echo intensity changes that are related to stress changes in the stretching tendon [7], and the stiffness-related changes in echo intensity first seen in tendon [9] are here confirmed as compliance-related changes in lung echo intensity.…”
Section: Discussionsupporting
confidence: 59%
“…Ultrasound imaging has previously been used in connective tissues to not only provide visual information about a tissue but also quantitatively describe its mechanical properties (i.e., by relating tissue mechanical properties to changes in echo intensity, or the grayscale brightness in the ultrasound image) [7][8][9][10]. Ultrasound is highly portable, inexpensive, noninvasive, and requires no radiation or contrast injection.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3A and B). A previous in vitro study reported that the mean echogenicity of tendons was non-linearly related to the applied tendon stress 32) . Nevertheless, the mean echogenicity of tendons increased during the relaxation period of a stress-relaxation test 33) .…”
Section: Discussionmentioning
confidence: 96%
“…The alteration in tendon echogenicity reflects changes in the cellular and extracellular composition of injured tendons along with the repair tissue, it ranged from a barely perceptible decrease in echogenicity with mild loss of fibre pattern as in mild tendonitis, to complete disruption of fibre pattern seen with fibre rupture accompanied with haemorrhage or with serious fluid accumulation and oedema (Denoix et al 2005;Duenwald et al 2011).…”
Section: Ultrasonographymentioning
confidence: 99%